Three‐dimensional bladder ultrasound to measure daily urinary bladder volume in hospitalized dogs. (31st July 2021) - Vasquez, Edward J.; Kendall, Allison; Musulin, Sarah; Vaden, Shelly L.
Abstract: Background: Urinary bladder volume (UBV) and urine residual volume (URV) provide important information for hospitalized dogs and might allow recognition of urine retention. Objective: Using 3‐dimensional (3D) ultrasound to monitor daily URV is a safe and effective way to recognize urinary retention. Animals: Twenty‐five client‐owned hospitalized dogs. Methods: Prospective, observational study. UBV and URV were measured using 3D ultrasound daily at approximately the same time. UBV was measured, the dog was taken for a 5‐minute controlled leash walk, then URV was estimated. Concurrent use of opioids, anesthetics, and fluids administered IV were recorded. Results: Daily URVs were >0.4 mL/kg in 22 of 25 dogs on at least 1 day of hospitalization. Seventeen of 25 dogs had an abnormal URV at the time of discharge. Of 18 dogs that were anesthetized while hospitalized, 16 had a URV >0.4 mL/kg with a mean of 4.34 mL/kg (range, 0.5‐13.4 mL/kg). No statistical difference in degree of URV was found based on the use of anesthesia, administration of fluids IV, or opioids. Weight was significantly associated with URV; dogs <10 kg had a higher URV per unit mass than dogs >10 kg ( P = .001). Conclusions and Clinical Importance: Use of a 3D ultrasound device to measure daily UBV and URV in hospitalized dogs provides a safe estimate of bladder volume in real‐time. Monitoring daily URV might help in early identification of patients that are retaining urine, thereby preventing potential adverse effects of urethral catheterization or prolonged urinary retention.